2017
DOI: 10.1063/1.5002663
|View full text |Cite
|
Sign up to set email alerts
|

Effects of finite-size neutrally buoyant particles on the turbulent flows in a square duct

Abstract: Interface-resolved direct numerical simulations of the particle-laden turbulent flows in a square duct are performed with a direct-forcing fictitious domain method. The effects of the finite-size particles on the mean and root-mean-square (RMS) velocities are investigated at the friction Reynolds number of 150 (based on the friction velocity and half duct width) and the particle volume fractions ranging from 0.78% to 7.07%. Our results show that the mean secondary flow is enhanced and its circulation center sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Some criteria for turbulence enhancement or attenuation in the literature. Costa et al 2018;Peng, Ayala & Wang 2019;Costa, Brandt & Picano 2020;Zhu et al 2020b), duct flows (Lin et al 2017a, ;Fornari et al 2018) and Couette flows (Wang, Abbas & Climent 2017). Lucci et al (2010) observed that particles larger than the Kolmogorov scale always reduced the average TKE of the decaying homogeneous isotropic turbulence, and attributed the reason to the particle-induced viscous dissipation near particle surfaces.…”
Section: Re Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Some criteria for turbulence enhancement or attenuation in the literature. Costa et al 2018;Peng, Ayala & Wang 2019;Costa, Brandt & Picano 2020;Zhu et al 2020b), duct flows (Lin et al 2017a, ;Fornari et al 2018) and Couette flows (Wang, Abbas & Climent 2017). Lucci et al (2010) observed that particles larger than the Kolmogorov scale always reduced the average TKE of the decaying homogeneous isotropic turbulence, and attributed the reason to the particle-induced viscous dissipation near particle surfaces.…”
Section: Re Pmentioning
confidence: 99%
“…Two mesh resolutions with respect to the particle size, d p /Δx = 12.8 and 19.2, are used in our simulations, which are comparable to those employed by Uhlmann (2008) and Santarelli & Fröhlich (2015). The accuracy of our DF/FD code for the single-phase turbulent channel and duct flows were validated in Yu et al (2016bYu et al ( , 2019 and Lin et al (2017a). Zhu et al (2020b) showed that the turbulence statistics for a vertical particle-laden channel flow obtained from d p /Δx = 12.8 were in good agreement with those from d p /Δx = 25.6.…”
Section: Simulation Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, particle-resolved DNS (PR-DNS) was made possible due to the developments of more powerful supercomputers and better numerical algorithms (Maxey 2017). Particle-laden homogeneous isotropic turbulence (HIT) (Ten Cate et al 2004;Burton & Eaton 2005;Lucci, Ferrante & Elghobashi 2010;Xu & Subramaniam 2010;Botto & Prosperetti 2012;Gao, Li & Wang 2013;Vreman 2016), homogeneous shear turbulence (Tanaka & Teramoto 2015), turbulent channel flows (Uhlmann 2008;Shao, Wu & Yu 2012;Picano, Breugem & Brandt 2015;Wang et al 2016b;Eshghinejadfard et al 2017), turbulent pipe flows (Wu, Shao & Yu 2011;Gupta, Clercx & Toschi 2018;Peng & Wang 2019) and turbulent duct flows (Lin et al 2017;Fornari et al 2018) were extensively investigated via different numerical methods. These studies focused on the particle size effect, but the effects of particle-to-fluid density ratio and particle sedimentation have also been examined to some extent (Shao et al 2012;Fornari et al 2016;Yu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are two research groups that have used this method to study particle-laden flows in a square duct. Lin et al 25 performed DNS with a direct-forcing fictitious domain method to consider the effect of finite-sized neutrally buoyant particles on the turbulence in a square duct with a relatively high particle volume fraction (∅ = 0.008 − 0.07), with their results showing that particles preferentially concentrate in the duct corner regions, and that the presence of particles enhances the mean secondary flow, with its vortex centre shifting closer to the duct core regions. Fornari et al 26 also discussed turbulence modulation by such particles using DNS combined with an immersed boundary method but considered a wider range of particle volume fractions (∅ = 0.0 − 0.2).…”
Section: Introductionmentioning
confidence: 99%